A study on the optimal load of wingate test for elite men's freestyle wrestlers - Liu, M.; Guo, Z.-X.; Chen, Y.; Zhou, L.-M.-F.; Bao, D.-P.; Liu, H.-Y. (Medicine & Science in Sports & Exercise, 2022)
The 30s Wingate Anaerobic Test (WAnT) is a common evaluation method used by elite athletes to evaluate the training effect of anaerobic exercise capacity. However, the commonly used 7.5% body weight is used as the WAnT load in wrestling, judo and other confrontation events. It often fails to faithfully reflect the improvement of training ability, which leads to the phenomenon of "false negative" in the judgment of training effect.